Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To find the axis of symmetry for the given parabola [tex]\( y = -x^2 - 2x + 6 \)[/tex], you can follow these steps:
1. Identify the coefficients of the quadratic equation: The given quadratic equation can be written in standard form [tex]\( y = ax^2 + bx + c \)[/tex], which makes it clear that:
- [tex]\( a = -1 \)[/tex]
- [tex]\( b = -2 \)[/tex]
- [tex]\( c = 6 \)[/tex]
2. Use the formula for the axis of symmetry: For a parabola given by [tex]\( y = ax^2 + bx + c \)[/tex], the axis of symmetry is given by the formula [tex]\( x = -\frac{b}{2a} \)[/tex].
3. Substitute the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] into the formula:
- [tex]\( a = -1 \)[/tex]
- [tex]\( b = -2 \)[/tex]
The formula becomes:
[tex]\[ x = -\frac{-2}{2 \cdot -1} \][/tex]
4. Simplify the expression: Calculate the value inside the fraction.
[tex]\[ x = -\frac{-2}{-2} \][/tex]
5. Calculate the final value:
[tex]\[ x = -1 \][/tex]
Therefore, the axis of symmetry for the parabola [tex]\( y = -x^2 - 2x + 6 \)[/tex] is given by the equation:
[tex]\[ x = -1 \][/tex]
1. Identify the coefficients of the quadratic equation: The given quadratic equation can be written in standard form [tex]\( y = ax^2 + bx + c \)[/tex], which makes it clear that:
- [tex]\( a = -1 \)[/tex]
- [tex]\( b = -2 \)[/tex]
- [tex]\( c = 6 \)[/tex]
2. Use the formula for the axis of symmetry: For a parabola given by [tex]\( y = ax^2 + bx + c \)[/tex], the axis of symmetry is given by the formula [tex]\( x = -\frac{b}{2a} \)[/tex].
3. Substitute the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] into the formula:
- [tex]\( a = -1 \)[/tex]
- [tex]\( b = -2 \)[/tex]
The formula becomes:
[tex]\[ x = -\frac{-2}{2 \cdot -1} \][/tex]
4. Simplify the expression: Calculate the value inside the fraction.
[tex]\[ x = -\frac{-2}{-2} \][/tex]
5. Calculate the final value:
[tex]\[ x = -1 \][/tex]
Therefore, the axis of symmetry for the parabola [tex]\( y = -x^2 - 2x + 6 \)[/tex] is given by the equation:
[tex]\[ x = -1 \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.